Two Drugs Have Potential to Slow Progression of Atherosclerosis - Alexander, Lori (MD Conference Express, 2008)
Two ASTEROID and STRADIVARIUS trials explored the potential for pharmacologic therapy to slow the progression of atherosclerosis or even cause plaque regression in patients with coronary artery disease. The studies involved different classes of drugs and different imaging modalities to evaluate the change in the degree of stenosis caused by the atherosclerotic plaque.